Body mass‐related changes in mammal community assembly patterns during the late Quaternary of North America. Issue 1 (8th October 2020) - Pineda‐Munoz, Silvia; Jukar, Advait M.; Tóth, Anikó B.; Fraser, Danielle; Du, Andrew; Barr, W. Andrew; Amatangelo, Kathryn L.; Balk, Meghan A.; Behrensmeyer, Anna K.; Blois, Jessica; Davis, Matt; Eronen, Jussi T.; et al.
Abstract : The late Quaternary of North America was marked by prominent ecological changes, including the end‐Pleistocene megafaunal extinction, the spread of human settlements and the rise of agriculture. Here we examine the mechanistic reasons for temporal changes in mammal species association and body size during this time period. Building upon the co‐occurrence results from Lyons et al. (2016) – wherein each species pair was classified as spatially aggregated, segregated or random – we examined body mass differences (BMD) between each species pair for each association type and time period (Late Pleistocene: 40 000 14 C–11 700 14 C ybp, Holocene: 11 700 14 C–50 ybp and Modern: 50–0 yr). In the Late Pleistocene and Holocene, the BMD of both aggregated and segregated species pairs was significantly smaller than the BMD of random pairs. These results are consistent with environmental filtering and competition as important drivers of community structure in both time periods. Modern assemblages showed a breakdown between BMD and co‐occurrence patterns: the average BMD of aggregated, segregated and random species pairs did not differ from each other. Collectively, these results indicate that the late Quaternary mammalian extinctions not only eliminated many large‐bodied species but were followed by a re‐organization of communities that altered patterns of species coexistence and associated differences in body size.